Analisis Faktor-Faktor Yang Mempengaruhi Loyalitas Nasabah Tabungan Bunaken Pada PT. Bank SulutGo Kantor Cabang Pembantu Ranotana - Turuis, Tanri Faiz (Universitas Sam Ratulangi, 2019)
The results of the analysis and hypothesis testing show that partially the service quality variables have a significant effect on customer loyalty, the product quality variable partially has a significant effect on customer loyalty and the price variable does not significantly influence loyalty.Then simultaneously the variable quality of service, product quality and price significantly influence the loyalty of customers of Bunaken savings products at PT. Bank SulutGo Ranotana Sub-Branch OfficeKeywords: Service Quality, Product Quality, Price and Loyalty